Assessment of the structural and functional diversities of plant microbiota: Achievements and challenges – A review - Hartmann, Anton (J Adv Res, 2019)
Analyses of the spatial localization and the functions of bacteria in host plant habitats through in situ identification by immunological and molecular genetic techniques combined with high resolving microscopic tools and 3D-image analysis contributed substantially to a better understanding of the functional interplay of the microbiota in plants. Among the molecular genetic methods, 16S-rRNA genes were of central importance to reconstruct the phylogeny of newly isolated bacteria and to localize them in situ. However, they usually do not allow resolution for phylogenetic affiliations below genus level. Especially, the separation of opportunistic human pathogens from plant beneficial strains, currently allocated to the same species, needs genome-based resolving techniques. Whole bacterial genome sequences allow to discriminate phylogenetically closely related strains. In addition, complete genome sequences enable strain-specific monitoring for biotechnologically relevant strains. In this mini-review we present high resolving approaches for analysis of the composition and key functions of plant microbiota, focusing on interactions of diazotrophic plant growth promoting bacteria, like Azospirillum brasilense, with non-legume host plants. Combining high resolving microscopic analyses with specific immunological detection methods and molecular genetic tools, including especially transcriptome analyses of both the bacterial and plant partners, enables new insights into key traits of beneficial bacteria-plant interactions in holobiontic systems.